Propagation and impacts on roadway of mining-induced far-field strong tremors: insights from numerical simulations - Han, Zepeng; Dou, Linming; Gong, Siyuan; Cao, Jinrong; Chen, Shuai; Hu, Bing; Li, Yongyuan; Zeng, Kezhi (Frontiers in Earth Science, 2024)
Mining-induced far-field mine tremors, which often cause strong ground tremors, are receiving more attention due to their increasing occurrence. Investigating the rock burst risk of roadway caused by those tremors is crucial to ensure production safety. In this study, Variational Mode Decomposition (VMD) was used to investigate the wave characteristics of strong mine tremors. The propagation and attenuation of these tremors were explored using the dynamic analysis of Flac3d. The amplification factor was introduced to assess the impact of these tremors on roadways. Plastic zone volume increment and Brittle Shear Ratio (BSR) are used to assess the roadway failure and the rock burst potential caused by these tremors, respectively. The main findings are as follows: (1) Compared with the main frequency of near-field mine tremor waveform, the far-field mine tremors waveform are mainly low frequency below 5Hz; (2) In the simulation, peak vibration velocities of P-wave and S-wave follow a power-law decay as the propagation distance increases, with P-wave attenuating faster than S-wave; (3) Under similar conditions, P-wave induce higher vibration velocities than S-wave, but S-wave generally exhibit a greater amplification factor than P-wave; (4) When the direction of dynamic load is consistent with the direction of maximum principal stress, the rock burst potential of roadway is higher, which explains the phenomenon that the rock burst potential of roadway under S-wave loading is higher than that under P-wave.